2018
DOI: 10.1016/j.humov.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Motor learning in children with developmental coordination disorder: The role of focus of attention and working memory

Abstract: Article 25fa pilot End User Agreement This publication is distributed under the terms of Article 25fa of the Dutch Copyright Act (Auteurswet) with explicit consent by the author. Dutch law entitles the maker of a short scientific work funded either wholly or partially by Dutch public funds to make that work publicly available for no consideration following a reasonable period of time after the work was first published, provided that clear reference is made to the source of the first publication of the work. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…In de study of van Abswoude et al (2015) verbal working memory capacity was related to performance improvements across groups. In contrast, in the study of van Van Cappellen -van Maldegem et al (2018) visuospatial working memory capacity was related to motor learning in the implicit group.…”
Section: Manipulation Checkmentioning
confidence: 57%
See 3 more Smart Citations
“…In de study of van Abswoude et al (2015) verbal working memory capacity was related to performance improvements across groups. In contrast, in the study of van Van Cappellen -van Maldegem et al (2018) visuospatial working memory capacity was related to motor learning in the implicit group.…”
Section: Manipulation Checkmentioning
confidence: 57%
“…Seven studies included children with a specific diagnosis or disorder as their target population. Two studies applied an errorless learning method (Capio, Poolton, Sit, Eguia et al, 2013;Van Abswoude et al, 2015), one used analogy learning (Tse & Masters, 2019), and four studies manipulated the focus of attention (Chiviacowsky et al, 2013;Saemi et al, 2013;Tse, 2017;Van Cappellen -van Maldegem et al, 2018). In four studies, the training was performed individually in the presence of the experimenter(s).…”
Section: Children With A-typical Development Study Characteristics and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the case of children, results of previous studies were inconsistent [11,14]. Some studies have reported no significant differences in motor learning between EF and IF, and some studies have reported that IF is more effective [15]. Emanuel et al [11] reported that IF is more effective than EF in transfer of children's motor skills.…”
Section: Discussionmentioning
confidence: 99%